GSK-3 Mouse Models to Study Neuronal Apoptosis and Neurodegeneration - Gomez-Sintes, Raquel; Hernandez, Felix; Lucas, Jose J.; Avila, Jesus (Frontiers in Molecular Neuroscience, 2011)
Increased GSK-3 activity is believed to contribute to the etiology of chronic disorders like Alzheimer’s disease, schizophrenia, diabetes and some types of cancer, thus supporting therapeutic potential of GSK-3 inhibitors. Numerous mouse models with modified GSK-3 have been generated in order to study the physiology of GSK-3, its implication in diverse pathologies and the potential effect of GSK-3 inhibitors. In this review we have focused on the relevance of these mouse models for the study of the role of GSK-3 in apoptosis. GKS-3 is involved in two apoptotic pathways, intrinsic and extrinsic pathways, and plays opposite roles depending on the apoptotic signaling process that is activated. It promotes cell death when acting through intrinsic pathway and plays an anti-apoptotic role if the extrinsic pathway is occurring. It is important to dissect this duality since, among the diseases in which GSK-3 is involved, excessive cell death is crucial in some illnesses like neurodegenerative diseases, while a deficient apoptosis is occurring in others such as cancer or autoimmune diseases. The clinical application of a classical GSK-3 inhibitor, lithium, is limited by its toxic consequences, including motor side effects. Recently, the mechanism leading to activation of apoptosis following chronic lithium administration has been described, involving NFAT/Fas signalling pathway. Understanding this mechanism could help to improve application of GSK-3 inhibitors to clinic by co-administering NFAT/Fas blockers and thus minimizing side effects. This would help to improve the use of GSK-3 inhibitors to the treatment of Alzheimer’s disease and to extend the application to other diseases.